2021
DOI: 10.2478/foecol-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nutrition of date palm: advances and applications. A review

Abstract: Foliar fertilization is one of the crucial ways for continued cultivation of date palm, obtaining the best results of growth and production, in addition to the possibility to reduce damage from abiotic stress. Although subjected date palm to an annual fertilization program, it faces some challenges, including low soil availability for nutrients, dryness of the soil surface, low root activity in the breeding period, soil alkalinity, as well as water scarcity in areas of cultivation, and symptoms of deficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Biostimulants, such as AMF, PGPR, and compost and manure, are regarded as potential substitutes for synthetic and chemical fertilizers, which can ensure food security and enable a sustainable product, thus paving the way to new approaches aiming at improving agricultural productivity [86,87]. Available data corroborate the positive impact of biostimulants on date palm, especially in terms of resilience to abiotic stress [88] (Table 2). In a study conducted by [30], the authors observed that growth traits, particularly the leaf number, plant height, and leaf area, were improved in date palm seedlings of the "Boufggous" variety subjected to drought, thanks to inoculation with Glomus monosporus, G. clarum, and G. deserticola.…”
Section: Biostimulants Attenuate Abiotic Stresses' Effects In Date Palmmentioning
confidence: 81%
“…Biostimulants, such as AMF, PGPR, and compost and manure, are regarded as potential substitutes for synthetic and chemical fertilizers, which can ensure food security and enable a sustainable product, thus paving the way to new approaches aiming at improving agricultural productivity [86,87]. Available data corroborate the positive impact of biostimulants on date palm, especially in terms of resilience to abiotic stress [88] (Table 2). In a study conducted by [30], the authors observed that growth traits, particularly the leaf number, plant height, and leaf area, were improved in date palm seedlings of the "Boufggous" variety subjected to drought, thanks to inoculation with Glomus monosporus, G. clarum, and G. deserticola.…”
Section: Biostimulants Attenuate Abiotic Stresses' Effects In Date Palmmentioning
confidence: 81%
“…Lessening the poisonous effects of excessive fertilizer application. Enhancing the activity of antioxidant enzymes to protect plants from the damaging effects of reactive oxygen species (Ragab et al, 2022;Shareef et al, 2023). According to previous studies, foliar application of Zno NPs reduces ROS by raising antioxidant enzyme levels.…”
Section: Introductionmentioning
confidence: 99%